Genealogy of Radicalism In Islamic Boarding Schools; Tracking the Potential for the Growth of Islamic Radicalism in Indonesia - Muhyidin, Muhyidin; Saidou , Ouedraogo (Darajatuna: Interdisciplinary Journal of Islamic Studies, 2025)
This article examines the genealogy of radicalism in Islamic boarding schools (pesantren) by tracing the historical, theological, and sociological factors that have the potential to give rise to the seeds of Islamic radicalism in Indonesia. As traditional Islamic educational institutions, pesantren play a strategic role in shaping the character and thinking of their students (santri). However, global dynamics, the infiltration of transnational ideologies, and rigid interpretations of religious texts can open up space for the influx of radical ideologies. This research uses a qualitative approach with critical discourse analysis, mapping the development of radicalism discourse from the colonial era, the New Order, and the reform era. The findings indicate that although the majority of pesantren espouse moderate Islam based on Ahlussunnah wal Jamaah, a small number are vulnerable to becoming fertile ground for radical ideology due to factors such as curriculum, alumni networks, and global political and economic relations. This article emphasizes the importance of strengthening religious moderation, monitoring transnational ideological flows, and revitalizing the role of pesantren as bastions of Islam rahmatan lil 'alamin (blessing for all the worlds).